Penerapan Terapi Butterfly Hug untuk Mengelola Kecemasan Ujian pada Remaja di SMP Negeri 9 Purwokerto - Wardhani, Debora Betty Dwi; Sundari, Ririn Isma; Apriliyani, Ita (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Adolescence is marked by physical and emotional changes that can increase the risk of anxiety disorders. The butterfly hug is a non-pharmacological relaxation technique to help control anxiety. Objective: This study aims to evaluate the effectiveness of butterfly hug therapy in reducing anxiety levels among 9th-grade students at SMP N 9 Purwokerto. Method: This activity was conducted at SMP N 9 Purwokerto on March 20, April 9, and April 17, 2025, targeting adolescents aged 12–18 years selected purposively based on mild to moderate anxiety levels measured by the Zung Self-Rating Anxiety Scale (ZSAS) and parental consent. The intervention applied the Butterfly Hug technique, consisting of crossing the arms on the chest and alternately tapping the shoulders combined with mindful breathing. The implementation included preparation (coordination with school and parents, preparation of educational materials), education (providing information on anxiety and demonstration of the Butterfly Hug), intervention sessions (guided individual and group practice), and evaluation (pre- and post-intervention ZSAS, observation, and feedback). Data were analyzed descriptively to assess changes in anxiety levels. Ethical principles were maintained, including informed consent, confidentiality, and voluntary participation. Result: The results show that the majority of respondents were 15 years old (51.4%) and male (51.4%). After the intervention, 31 students (88.6%) experienced a decrease in anxiety to the point of no anxiety, while 4 students (11.4%) decreased from moderate anxiety to mild anxiety. Conclusion: Butterfly hug therapy effectively reduces students' anxiety levels when facing exams.